Managing reality accountability and the miasma of private and public domains - Lehman, Cheryl R. (Advances in public interest accounting, 2013)
Accounting's contribution to reality construction is envisioned in this volume of critical research, examining accounting's role in contemporary issues: ethics, sustainability, financial instability, post SOX legislation, education, and performance appraisals to name a few. Do CEOs manage rather than reveal environmental liabilities in their never-ending quest for reporting earnings? Under the scrutiny of negative publicity, does the banking community revise images, mask impending crises, and distort regulatory processes? Will shifts in litigation risk influence financial reporting? How do demands and perceptions from powerful external stakeholders change education or organizational processes? How might accounting positively engage in social movements, grass-roots empowerment, and change? These are among the explorations in this volume through case studies, interviews, analysis and interdisciplinary perspectives. Exposing accounting's impact on major social struggles of our times, these works contribute to the debates by revealing that the discipline can be a vital technology in the tool box of governance, political, economic and social practice, holding a key for affirmation and empowerment.